Axonal mRNA localisation and the development of peripheral sensitisation in vitro - Arendt-Tranholm, Asta (2022)
Sensory neuronal cells of the dorsal root ganglia (DRG) are highly polarised cells, which receive and relay noxious signals from the periphery to the spinal cord. These sensory neuronal cells are capable of remarkable plasticity to adapt to the local environment and external stimuli. During periods of inflammation and in chronic pain states, the nociceptors are sensitised and consequently activated by lower thresholds of stimuli, in addition to firing of action potentials at a higher frequency. Multiple mechanisms have been shown to contribute to these events, including inflammatory mediators such as prostaglandin E2 (PGE2), which has been shown to be crucial in inducing a sensitised state. The neuroplasticity of sensory neurons is likely mediated by local regulation of translation which drives changes to the local proteome and neuronal function. In vitro studies have characterised a distinct neurite transcriptome unique to that of the cell body of the sensory neuronal cell. Changes to the local transcriptome, and local translation regulation in the axon, are hypothesised to facilitate quick adaptation in the periphery of sensory neuronal cells. The aim of this thesis was to characterise the local axonal transcriptome and to assess the changes in the axonal transcriptome in a PGE2-induced model of sensitisation of DRG-neurones. Embryonic (16.5) DRG-cells were exposed to 24-hours (H) 10μM PGE2, to create an in vitro model of sensitisation of peripheral nociceptors. The PGE2-protocol induced a significant increase in excitability to subsequent exposure to capsaicin, measured as calcium (Ca2+) transients, compared to vehicle-treated control DRG-cells. Additionally, the PGE2-protocol resulted in significantly higher expression of Ngf mRNA in the cell body, compared to control DRG-cells. The model was successfully replicated with adult (8WO) DRG cells, with an adjusted protocol of exposure to PGE2 for 12H. The data demonstrated a suitable in vitro model of sensitisation had been established. Porous membrane chambers were used to allow the separate extraction of RNA from the cell body or the axons of PGE2-exposed and control DRG-cells. This RNA was used for sequencing (RNAseq) to explore potential changes in the axonal transcriptome induced by PGE2. Comparison of the axonal transcriptome revealed considerable overlap in expression patterns between the control DRG-cells from embryonic and adult mice. Pathways associated with local translation, such as eIF2- and oxidative phosphorylation-signalling, characterised the axonal transcriptome of control E16.5 and 8WO DRG-cells. These results provide evidence for a compartmentalised transcriptome playing a key role in the functional adaptation of DRG-cells, possibly through local regulation of translation. The PGE2-sensitisation protocol induced significant changes to the local axonal transcriptome of DRG-cells from both embryonic and adult mice. Pathways previously associated with hyperalgesic priming of sensory neuronal cells, including IL-6- and cyclic AMP (cAMP)-mediated signalling, were identified as characteristic of the axonal transcriptome following PGE2-sensitisation. Overall, 23 RNAs were significantly increased in the axon following PGE2-sensitisation for both embryonic and adult mice. Bioinformatic analysis of the axonal transcriptome identified 3 RNAs, Arid5a, Cebpb, and Tnfrsf12a, associated with the sensitisation by PGE2 and predicted as potential localised therapeutic targets. Arid5a, AT-rich interactive domain-containing protein 5a, is an RNA-binding protein which has been identified to play a role in stabilising mRNAs associated with an inflammatory response through NF-κB and CREB. Cebpb, the transcription factor C/EBPβ, has been linked to the development of sensitisation in the central nervous system through cAMP-signalling and increased expression of nociceptive channels including the capsaicin receptor, transient receptor potential cation channel subfamily V member 1 (TRPV1). Tnfrsf12a mRNA encodes the tumour necrosis-like weak inducer of apoptosis (TWEAK) receptor, also known as Fibroblast growth factor inducible 14 (Fn14), associated with neurite regeneration following axotomy through NF-κB pathway activation. In the final study, the identified RNAs were knocked down in E16.5 DRG-cells with 24H siRNA treatment prior to induction of the model of PGE2 sensitisation. Knockdown of Tnfrsf12a RNA prevented PGE2-induced hyperexcitability to capsaicin. While underpowered, knockdown of Arid5a also reduced the PGE2-induced sensitisation of the capsaicin response. The results presented in this thesis characterise the similarities and differences in the axonal transcriptome of DRG-cells from embryonic and adult mice. The identified changes in the axonal transcriptome of nociceptors in the model of sensitisation, and the subsequent knockdown of specific RNAs successfully reducing excitability, support the further investigation of the local transcriptome and translation regulation for the development of novel analgesics.